HEALTH EDUCATION FOR STUDENT CADRES IN MIDDLE SCHOOL HEALTH CENTER TO IMPROVE THEIR KNOWLEDGE OF ADDITIONAL AND BALANCE NUTRITION - Bachtiar Rifai Pratita Ihsan; Valentina Yurina; Eva Putri Arfiani; Diah Royani Meisani; Luthfi Ahmad Muchlashi; Anita Puspa Widiyana (Caring : Jurnal Pengabdian Masyarakat, 2021)
Food additives are materials added to food to affect the nature or shape of the food. These condiments can cause adverse effects on health if being consumed every day more than the amount in mg/Kg body weight. In addition, there are food additives that are prohibited, such as boric acid, formalin, salicylic acid, and others. The lack of understanding of junior high school (SMP) students regarding food additives that are allowed and prohibited cause students to be more likely exposed to foods that contain harmful substances that will accumulate or cause negative effects in the long term. This Community Service Activity aims to improve the understanding of School Health Unit (UKS) cadre students regarding food additives and balanced nutrition. This activity was attended by students from SMPN 1 Singosari, SMP 4 Muhammadiyah Singosari, and SMP Islam Bani Hasyim Singosari. Before and after the counseling material regarding food additives and balanced nutrition, the level of understanding was measured using pre and post-tests. The test results were then analyzed using independent T-test statistics with a confidence level of 95.  The results of this activity indicate that there is an increase in participants' knowledge (40%) about food additives and balanced nutrition. Counseling is one of the ways to increase students' understanding of food additives as food safety and balanced nutrition is important to support growth and development.